Sclerotium rot - a new disease of vanilla (Vanilla planifolia Andrews) in India - Bhai, Joseph Thomas, R Suseela (Journal of Spices and Aromatic Crops, 2000)
A new type of bean rot affecting vanilla beans was observed in vanilla (Vanilla planifolia) growing tracts of Moovattupuzha in Emakulam District (Kerala, India). The disease was characterized by rotting of bean bunches and subsequent development of thick fungal mat over the bean surface. The causal organism was identified as Sclerotium rolfsii; the fungus was brought into pure culture and its pathogenicity was proved. This is the first report of the fungus on vanilla from India.